Simultaneous and collaborative development of satellites and Information Systems to support their lifecycle processes. Issue 111 (January 2023) - Silva, Ana Claudia de Paula; Loureiro, Geilson
Abstract: Space Systems Engineering is the domain in which satellites are developed. A lot of information gathered by the systems engineer to develop a space product is also necessary and gathered by the software engineer in the Software Engineering domain to develop the Information Systems that will support the lifecycle processes of that product. Motivated by this reality, this paper aims to demonstrate that the work of the software engineer can be integrated with that of the systems engineer during the Systems Engineering process. We assumed the use of Model-Based Systems Engineering (MBSE) and Systems Concurrent Engineering (SCE) as the approaches to engineering a satellite and looked at the activities performed by the systems engineer to identify how the software engineer's work can be inserted into the Systems Engineering process. We use the AMAZONIA 1 satellite to exemplify and focus on the process of assembly, integration and testing of this satellite. We concluded that simultaneous and collaborative work between the Systems Engineering and Software Engineering domains is feasible and can bring quality and productivity gains for both sides. Highlights: Information Systems are important tools to support satellites lifecycle processes. Satellites engineering information is also relevant to the Information Systems. Information Systems can be developed simultaneously with the satellites. Simultaneous and collaborative development is feasible and brings benefits.